1999
DOI: 10.1177/000331979905000708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Left Atrial Wall Elasticity Using Acoustic Microscopy

Abstract: Left atrial wall elasticity is one of the important factors regulating left atrial stiffness and functions. The authors evaluated left atrial wall elasticity by measuring the sound speed through the left atrial wall, based on the hypothesis that high elasticity tissues will yield larger sound speed values through the tissue, and examined age-associated changes in left atrial wall elasticity. Left atrium specimens were obtained from 30 normal subjects (age, 15-95 years) at autopsy. An acoustic microscope, opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…There may be a correlation between ventricular and atrial remodeling since NTpro-BNP levels and ejection fraction were found to be related with atrial asynchrony [19,20]. Aging may lead to histological changes in the atrium [9,21], However, in the present study, we have found by color TDI that longitudinal left atrial function parameters were not affected in obese adults. Since no previous similar study assessing atrial functions in obesity by color TDI was present, we don't have any other data for comparison of our results.…”
Section: Discussioncontrasting
confidence: 60%
“…There may be a correlation between ventricular and atrial remodeling since NTpro-BNP levels and ejection fraction were found to be related with atrial asynchrony [19,20]. Aging may lead to histological changes in the atrium [9,21], However, in the present study, we have found by color TDI that longitudinal left atrial function parameters were not affected in obese adults. Since no previous similar study assessing atrial functions in obesity by color TDI was present, we don't have any other data for comparison of our results.…”
Section: Discussioncontrasting
confidence: 60%
“…From this measurement, we could demonstrate that LA compliance is a major contributing factor in the determination of LA pressure in patients with MS, along with mitral gradient. Although the determinants of LA compliance were not identified in this study, previous study [13] using direct measurement of LA wall elasticity by acoustic microscopy at autopsy specimens of patients without heart disease has shown that LA stiffness increased with advancing age, that corresponded with pathophysiologic findings of an increase in interstitial collagen. Therefore, age is the important determinant of LA compliance.…”
Section: Discussionmentioning
confidence: 54%
“…6,7,40 However, several and recent findings suggest that the degree of elevated LV filling pressures may not fully explain LA failure and that LA myocardial fibrosis may play a role in the systolic and diastolic dysfunction of the left atrium. [8][9][10][11] In this respect, in our study, noninvasive LV filling pressures were modestly associated with LA systolic and diastolic function. According to these findings, previous reports have also demonstrated a modest association between LV filling pressures and LA function.…”
Section: La Systolic and Diastolic Function In Patients With Hfnefmentioning
confidence: 84%
“…6,7 However, several and recent studies suggest that the degree of elevated LV filling pressures may not fully explain LA failure and that LA myocardial fibrosis may play a role in the systolic and diastolic dysfunction of the left atrium. [8][9][10][11] It is well known that LV interstitial fibrosis as a consequence of comorbid conditions, such as type 2 diabetes, obesity, hypertension, and previous history of coronary artery disease (CAD), affects primarily the subendocardial systolic and diastolic function of the left ventricle (i.e., LV longitudinal systolic and diastolic function). [12][13][14][15][16][17][18][19][20] In that regard, we hypothesized that in patients with HFNEF as a result of elevated prevalence of comorbidities (i.e., type 2 diabetes, obesity, hypertension, and history of CAD), the same fibrotic processes that affect the subendocardial layer of the left ventricle could also alter the subendocardial fibers of the left atrium.…”
mentioning
confidence: 99%